2015
DOI: 10.3109/03008207.2015.1077239
|View full text |Cite
|
Sign up to set email alerts
|

Cripto-1: an extracellular protein – connecting the sequestered biological dots

Abstract: Cripto-1 (CR-1) is a multifunctional embryonic protein that is re-expressed during inflammation, wound repair, and malignant transformation. CR-1 can function either as a tethered co-receptor or shed as a free ligand underpinning its flexible role in cell physiology. CR-1 has been shown to mediate cell growth, migration, invasion, and induce epithelial to mesenchymal transition (EMT). The main signaling pathways mediating CR-1 effects include Nodal-dependent (Smad2/3) and Nodal-independent (Src/p44/42/Akt) sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…ACVR1B-645H,) were purchased from the indicated vendors. CR1/BP interaction assays were run in parallel to that described previously by Klauzinska and colleagues (19). In brief, four different target proteins (Nodal, GRP78, ACVR1B/Alk4, and BSA) were solid phased to a 96-well plate (Costar, catalog no.…”
Section: Ihc Staining and Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…ACVR1B-645H,) were purchased from the indicated vendors. CR1/BP interaction assays were run in parallel to that described previously by Klauzinska and colleagues (19). In brief, four different target proteins (Nodal, GRP78, ACVR1B/Alk4, and BSA) were solid phased to a 96-well plate (Costar, catalog no.…”
Section: Ihc Staining and Scoringmentioning
confidence: 99%
“…ab103891), and 50 mL goat anti-rabbit IgG-HRP (Santa Cruz Biotechnology, catalog no. sc-2004) according to the procedure published previously (19). A PBS wash and 30-minute room temperature rotary shaker incubation was performed between each treatment following CR1 addition.…”
Section: Ihc Staining and Scoringmentioning
confidence: 99%
“…Cripto-1 and Cryptic mediate the binding of GDF1 and GDF3 to the same receptors as Nodal, whereas other TGFβ superfamily ligands such as Activin-βA and –βB can signal through Alk4 and ActRIIA or ActRIIB without co-receptor requirement but are inhibited by the presence of Cripto-1 [7, 2226]. Therefore, Cripto-1/Cryptic mediate signaling specificity among TGFβ superfamily ligands and Cripto-1 is also capable of inducing signaling of other pathways [2732]. Of note however, although Cripto-1 involvement in Nodal signaling is well established, Cripto-1 independent signaling by Nodal has also been demonstrated.…”
Section: Canonical Nodal Signaling and Biological Rolesmentioning
confidence: 99%
“…14,22 However, here we have shown that cripto-1 antibodies available commercially provide different results, pending cell type, downstream processing (such as fixation) and cellular assay. 14,22 However, here we have shown that cripto-1 antibodies available commercially provide different results, pending cell type, downstream processing (such as fixation) and cellular assay.…”
Section: Discussionmentioning
confidence: 77%
“…[4][5][6][7] In the healthy adult, cripto-1 expression has been suggested to be turned off or, in some cases, reduced to only a small population of adult stem cells. 14 Detection of cripto-1 as a cancer biomarker relies on the specificity and sensitivity of the different cripto-1 antibodies. 3,[10][11][12][13] Due to the seemingly low expression of cripto-1 in healthy individuals and that it might be highly re-expressed in cancer cells, cripto-1 has become a popular subject in biomarker discovery in various cancers.…”
Section: Introductionmentioning
confidence: 99%